Studies on Homalomeneae (Araceae) of Peninsular Malaysia IV: Homalomena stongensis, a remarkable new species endemic to Gunung Stong, Kelantan - Zulhazman Hamzah; Peter C. Boyce; Mashhor Mansor (2012)
Homalomena stongensis is described from Gunung Stong, Kelantan, where it is very locally endemic to steep forested slopes. An updated key to Peninsular Malaysian species of Homalomena Supergroup Homalomena is provided, and the new species is illustrated